Characterization of Nocardia asteroides Isolates from Different Ecological Habitats on the Basis of Repetitive Extragenic Palindromic-PCR Fingerprinting - Yamamura, Hideki (American Society for Microbiology, 2004)
Thirteen isolates of Nocardia asteroides from both soils and aquatic samples (lake and moat sediments, as well as scum from activated sludge), together with a type strain and two known clinical isolates of this species, were characterized by repetitive extragenic palindromic-PCR fingerprinting with the BOX-A1R primer. The resulting DNA fingerprint patterns proved to be strain specific, and cluster analysis distinguished the soil isolates, the aquatic isolates, and the known strains as being in separate groups.